Carbon material as well as preparation method and application thereof
By introducing carbon ring-containing lipids or amide compounds into the carbon material and lead paste active substances, the problems of sulfation and hydrogen precipitation of lead acid batteries are solved, and the battery cycle life is improved and internal resistance is reduced.
Patent Information
- Application Number
- CN202311154371.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-11
AI Technical Summary
The rapid shallow charge and discharge of lead-acid batteries in part charge states lead to the sulfation of the electrode active substance, forming large-particle lead sulfate crystals, hindering the transmission of electrons and electrolytes, reducing the utilization rate of electrode active substances, and the addition of carbon materials will lead to hydrogen precipitation problems.
Lipids or amide compounds containing carbon rings are introduced into the surface and pores of carbon materials and into the active substances of lead paste. By adsorbing the carbon ring onto the surface of carbon materials in a closed state in a low pH environment, the hydrogen evolution overpotential is increased, and the carbon ring opens the ring in a high pH environment to produce long carbon chain organic matter containing carboxyl groups, affecting the binding energy of lead ions and sulfate and improving the crystallization process and state of lead sulfate.
Reduce the precipitation of hydrogen in the electrolyte, reduce the consumption of the electrolyte, improve the cycle life of the battery, and refine the lead sulfate grains, reduce the internal resistance of the battery, and improve the sulfation process of the battery.
Abstract
Description
Technical Field
[0001] The present application relates to a carbon material and a preparation method and application thereof, belonging to the field of conductive materials. Background Art
[0002] Lead-acid battery is a battery commonly used for vehicle start-stop. This application environment requires the battery to maintain good and stable battery performance under high power output and partial charge state. However, under partial charge state, the lead-acid battery will cause sulfation of its electrode active material after rapid and repeated shallow charge and discharge. The sulfation process refers to the gradual accumulation and growth of lead sulfate particles, which cannot be eliminated by a short period of charging and form large lead sulfate crystals. These crystals will hinder the transmission of electrons and electrolytes, resulting in a decrease in the utilization rate of electrode active materials. In order to cope with this situation, lead-carbon batteries came into being. By adding a certain amount of carbon material to the negative active material of the lead-acid battery, the conductivity of the battery in the discharge state can be improved, thereby improving its rate performance and cycle stability. However, the addition of carbon materials will cause the problem of hydrogen precipitation at the negative electrode. Therefore, how to reduce the amount of hydrogen precipitation of carbon materials while solving the battery sulfation problem is the focus and difficulty of lead-acid battery research. Summary of the invention
[0003] In order to solve the problem of low hydrogen evolution overpotential of carbon materials in lead-carbon batteries leading to hydrogen evolution at electrodes and the problem of electrode sulfation, the present invention provides a certain degree of improvement in battery performance by introducing a certain amount of carbocyclic-containing lipids and / or amide compounds into the surface and pores of carbon materials and into the active substances of lead paste. Among them, in a low pH environment (pH<=7), the carbon rings of the carbon ring-containing lipid or / and amide compounds are in a closed state, and adsorption on the surface of the carbon material helps to increase the hydrogen evolution overpotential of the carbon material. Reducing the precipitation of hydrogen in the electrolyte can reduce the consumption of the electrolyte and increase the cycle life of the battery. In a high pH (pH>7) environment (at the end of the battery discharge, a large number of sulfate groups combine with lead ions to form lead sulfate crystals. The migration rate of hydrogen ions is usually greater than that of lead ions. In order to ensure the ionization balance of the electrolyte, a large number of hydrogen ions combine with sulfate ions, and the remaining hydroxide groups make the micropores of the electrode active material present an alkaline environment), the carbon ring is in an open state, and the open product is a long carbon chain organic matter containing a carboxyl group. After the opening, the carboxyl group contained in the organic carbon chain can react with the lead ion, affecting the binding energy of the lead ion and the sulfate group, thereby improving the crystallization process and state of the lead sulfate, and refining the lead sulfate grains, so as to reduce the internal resistance of the battery, improve the sulfation process of the battery, and increase the cycle life of the battery.
[0004] According to one aspect of the present application, a carbon material is provided, wherein the carbon material contains organic matter containing a carbon ring;
[0005] The content of the carbon ring-containing organic matter in the carbon material is 1 to 30 wt %;
[0006] The molecular weight of the carbon ring-containing organic matter is 90-500.
[0007] The carbocyclic organic matter is selected from at least one of a carbocyclic lactone organic matter and a carbocyclic amide organic matter;
[0008] The carbocyclic lactone organic substance is selected from at least one of γ-butyrolactone, γ-valerolactone, coumarin, and thiamin;
[0009] The carbon ring-containing amide organic compound is selected from at least one of benzamide, dansamide, o-amide and furamide.
[0010] According to another aspect of the present application, a method for preparing the above-mentioned carbon material is provided, comprising the following steps:
[0011] The raw materials containing organic matter containing carbon rings, activated carbon material, sulfuric acid and solvent are mixed and dried to obtain the carbon material.
[0012] Optionally, the following steps are included:
[0013] The organic matter containing the carbon ring is mixed with a solvent to obtain a mixed solution, and then sulfuric acid and an activated carbon material are added to the mixed solution in sequence, stirred, and dried to obtain the carbon material.
[0014] The activated carbon material is selected from at least one of coal-based activated carbon, wood-based activated carbon, synthetic activated carbon, and biomass activated carbon;
[0015] The specific surface area of the activated carbon material is 300 to 3000 m 2 / g;
[0016] The solvent is a mixed solution of water and ethanol;
[0017] In the solvent, the volume ratio of water to ethanol is 1:0.01-100.
[0018] The ratio of the carbon ring-containing organic matter to the solvent is 0.01-50 g: 20-2000 ml;
[0019] The usage ratio of the sulfuric acid to the solvent is 0.1-100 ml: 20-2000 ml;
[0020] The usage ratio of the carbon ring-containing organic matter to the activated carbon material is 0.01-50g:1-1000g.
[0021] The drying temperature is 40-150°C;
[0022] The drying time is 1 to 48 hours.
[0023] According to another aspect of the present application, an electrode is provided, wherein the electrode contains the above-mentioned carbon material.
[0024] According to another aspect of the present application, a lead-acid battery is provided, wherein the lead-acid battery contains the above-mentioned electrode.
[0025] The beneficial effects of this application include:
[0026] In a low pH environment (pH<=7), the carbon rings of the carbon ring-containing lipid or / and amide compounds are in a closed state, and adsorption on the surface of the carbon material helps to increase the hydrogen evolution overpotential of the carbon material. Reducing the precipitation of hydrogen in the electrolyte can reduce the consumption of the electrolyte and increase the cycle life of the battery. In a high pH (pH>7) environment (at the end of the battery discharge, a large number of sulfate groups combine with lead ions to form lead sulfate crystals. The migration rate of hydrogen ions is usually greater than that of lead ions. To ensure the ionization balance of the electrolyte, a large number of hydrogen ions combine with sulfate ions, and the remaining hydroxide groups make the micropores of the electrode active material present an alkaline environment), the carbon ring is in an open state, and the open product is a long carbon chain organic matter containing a carboxyl group. After the opening of the ring, the carboxyl group contained in the organic carbon chain can react with the lead ion, affecting the binding energy of the lead ion and the sulfate group, thereby improving the crystallization process and state of the lead sulfate, refining the lead sulfate crystals, and achieving the purpose of reducing the internal resistance of the battery, improving the sulfation process of the battery, and increasing the cycle life of the battery. DETAILED DESCRIPTION
[0027] Unless otherwise specified, the raw materials in the examples were purchased from commercial sources and used directly without further treatment; the instruments and equipment used were based on the parameters recommended by the manufacturer.
[0028] In the embodiment, the cycle life of the lead-carbon battery is tested using a Blue Power charge and discharge tester and a Newway charge and discharge tester.
[0029] In the embodiment, the mass percentage of the organic matter to the mass percentage of the entire carbon material is measured by thermogravimetric method.
[0030] Example 1
[0031] Step 1: Prepare the composite carbon material by the following method:
[0032] 1. Dissolve 2g of γ-butyrolactone in 200ml of a mixture of ultrapure water and ethanol, where the volume ratio of ethanol to water is 1:1 to form solution A. 2. Add 10ml of 20% sulfuric acid solution to solution A. 3. Add 10g of 1300m 2 / g of activated carbon material to form a mixed solution B. 4. Stir solution B thoroughly to disperse the carbon material evenly and dry it in an environment of 80°C. According to the test, the organic matter in the prepared carbon material accounts for 18% of the whole material.
[0033] Step 2: Prepare lead-carbon battery electrodes and lead-carbon batteries by the following method and conduct cycle stability and gas evolution tests:
[0034] 1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10 minutes to obtain lead paste; (2) Scrape the lead paste onto a metal lead grid with a size of 70mm long, 50mm wide, and 2mm thick, and cure and dry to obtain a lead-carbon battery negative electrode. The curing temperature is 40°C, the humidity is 80%, and the curing time is 20 hours; the drying temperature is 80°C, and the time is 24 hours;
[0035] 2) Preparation of the positive electrode: The positive electrode of the lead-acid battery is prepared according to the same process steps as the negative electrode preparation steps (1) and (2), except that no carbon material is added to the positive electrode;
[0036] 3) Preparation of lead-carbon battery: three positive plates and two negative plates are placed in parallel with each other in an alternating manner, and a colloidal PE separator for lead-carbon battery is placed between the positive plates and the negative plates, and two negative plates are welded in parallel and three positive plates are welded in parallel respectively. The total mass of positive active material of the lead-acid battery (the total mass of the lead paste on the three positive plates after drying) is 60.0g, and the total mass of positive active material refers to the total mass of the lead paste contained in the three positive plates welded in parallel. The total mass of negative active material (the total mass of the lead paste on the two negative plates after drying) is 52.9g, and the total mass of negative active material refers to the total mass of the lead paste contained in the two negative plates welded in parallel. The positive and negative electrode grids are conventional lead grids with dimensions of 70 mm long, 50 mm wide and 2 mm thick. The positive and negative electrodes are placed in a tightly assembled battery box with a length of 76 mm, a width of 40 mm and a height of 100 mm. 83 g of the sulfuric acid electrolyte prepared above with a mass concentration of 1.275 g / ml is injected into the battery box.
[0037] The battery was tested for life at room temperature. The test conditions were: 4.2A constant current discharge for 59 seconds, 18A discharge for 1 second, 6.3A current 2.3V constant current constant voltage charge for 60 seconds at 25°C. The charge and discharge conditions were cycled 3600 times, then left to stand for 40 hours, and then restarted after 40 hours. The termination condition of the life test was that the battery voltage dropped below 1.2V. The assembled internal hybrid battery can run 40682 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the assembled lead-carbon battery can reach 5.7 times the life of traditional lead-acid batteries.
[0038] The battery was tested for gas evolution at room temperature, and the test method was as follows: the battery was fully sealed with laboratory-specific commercial paraffin, and then an air duct was inserted into the exhaust port of the battery. The end of the air duct located inside the battery passed through the rubber plug with a length of 5 mm, and the end of the air duct located outside the working electrode chamber was introduced into the device for testing the gas volume by the water displacement method. The inner and outer surfaces of the rubber plug through which the air duct passed and various connections between the air duct and the commercial water displacement method gas volume test device were firmly sealed with commercial AB glue, in order to ensure that the gas generated by the battery end was completely introduced into the commercial water displacement method gas volume measurement device, and the gas volume generated by the battery end was collected by the device, and the gas production rate was calculated. During the test, the battery system was placed in a constant temperature environment of 25°C, and a constant voltage of 2.4V was applied to both ends of the battery for 48 hours. It was calculated that the gas production rate of the lead-carbon battery of the carbon material of this formula was 0.16ml / (wh·h).
[0039] Example 2
[0040] According to the requirements of Example 1, without changing other conditions, the addition amount of step 1, 1.γ-butyrolactone is changed to 0.6g. After testing, the organic matter in the prepared carbon material accounts for 5% of the whole material. The assembled internal hybrid battery can run 31365 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.4 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.28ml / (wh·h).
[0041] Example 3
[0042] According to the requirements of Example 1, without changing other conditions, the addition amount of step 1, 1.γ-butyrolactone is changed to 3g. After testing, the organic matter in the prepared carbon material accounts for 28% of the whole material. The assembled internal hybrid battery can run 28444 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.0 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.26ml / (wh·h).
[0043] Example 4
[0044] According to the requirements of Example 1, without changing other conditions, step 1, 3. activated carbon was replaced with a specific surface area of 500m 2 / g of activated carbon, after testing, the organic matter in the prepared carbon material accounts for 4% of the whole material. The assembled internal hybrid battery can run 28509 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.0 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in room temperature environment is 0.24ml / (wh·h).
[0045] Example 5
[0046] According to the requirements of Example 1, without changing other conditions, step 1, 3. activated carbon was replaced with a specific surface area of 2500m 2 / g of activated carbon, and after testing, the organic matter in the prepared carbon material accounts for 25% of the entire material. The assembled internal hybrid battery can run 34072 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.7 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.22ml / (wh·h).
[0047] Example 6
[0048] According to the requirements of Example 1, without changing other conditions, the volume ratio of alcohol to water in step 1, 1. the blend of water and ethanol is 10:1 to form a solution. After testing, the organic matter in the prepared carbon material accounts for 5% of the entire material. The assembled internal mixed battery can run 37309 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal mixed lead-carbon battery can reach 5.2 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.30ml / (wh·h).
[0049] Example 7
[0050] According to the requirements of Example 1, without changing other conditions, the volume ratio of alcohol to water in step 1, 1. the blend of water and ethanol is 1:10 to form a solution. After testing, the organic matter in the prepared carbon material accounts for 25% of the entire material. The assembled internal mixed battery can run 20786 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal mixed lead-carbon battery can reach 2.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.27ml / (wh·h).
[0051] Example 8
[0052] According to the requirements of Example 1, without changing other conditions, step 1, 1.γ-butyrolactone is replaced with the same mass of γ-valerolactone. After testing, the organic matter in the prepared carbon material accounts for 15% of the whole material. The assembled internal hybrid battery can run 38116 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 5.3 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.24ml / (wh·h).
[0053] Example 9
[0054] According to the requirements of Example 1, without changing other conditions, step 1, 1. γ-butyrolactone is replaced with benzamide of the same mass. After testing, the organic matter in the prepared carbon material accounts for 16% of the entire material. The assembled internal hybrid battery can run 34992 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 4.9 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.25ml / (wh·h).
[0055] Example 10
[0056] According to the requirements of Example 1, without changing other conditions, step 1, 1.γ-butyrolactone is replaced with a mixture of 1gγ-butyrolactone and 1g benzamide. After testing, the organic matter in the prepared carbon material accounts for 20% of the entire material. The assembled internal hybrid battery can run 37156 cycles in the normal temperature life test. Compared with the test results of ordinary lead-acid batteries with the same lead content under the same test conditions (7200 cycles), the normal temperature cycle life of the internal hybrid lead-carbon battery can reach 5.2 times the life of traditional lead-acid batteries. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.31ml / (wh·h).
[0057] In combination with the above embodiments, it can be found that the specific surface area of the carbon material, the amount of organic matter added, and the amount of ethanol added during the introduction of organic matter have a great influence on the content of organic matter in the prepared carbon composite material. The larger the specific surface area of the carbon material, the higher the content of organic matter, the larger the content of ethanol, and the higher the amount of organic matter introduced.
[0058] Comparative Example 1
[0059] Lead-acid battery: According to the requirements of Example 1, without changing other conditions, step 2 "1) Preparation of negative electrode: (1) Premix 600g lead powder, 9g prepared carbon material, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" was changed to (without adding any carbon material) "1) Preparation of negative electrode: (1) Premix 600g lead powder, 8.4g barium sulfate, and 0.3g polypropylene short fiber with a length of 5mm and a diameter of 0.5-1.5μm in a high-speed mixer, add 84g deionized water to the premixed powder while stirring, and continue stirring for 10min to obtain lead paste;" without adding other steps, and the lead-acid battery was prepared. The assembled internal hybrid battery can run 7200 cycles in the normal temperature life test. Lead-acid batteries do not have hydrogen evolution problems, so gas generation rate testing is not performed.
[0060] Comparative Example 2
[0061] Lead-carbon battery: According to the requirements of Example 1, other conditions were not changed, and the composite carbon material was not prepared. A lead-carbon battery with a specific surface area of 1300 m 2 / g of activated carbon is used as a carbon material additive for lead-carbon batteries. The assembled internal hybrid battery can run 10,800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.40ml / (wh·h).
[0062] Comparative Example 3
[0063] According to the requirements of Example 1, without changing other conditions, the amount of γ-butyrolactone added in step 1 was changed to 0g, and the assembled internal hybrid battery could run 10800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in the room temperature environment was 0.41ml / (wh·h).
[0064] Comparative Example 4
[0065] According to the requirements of Example 1, without changing other conditions, step 1, 3. activated carbon was replaced with a specific surface area of 20m 2 / g of activated carbon, after testing, the organic matter in the prepared carbon material accounts for 80% of the whole material, due to the excessive addition of γ-butyrolactone, the internal resistance of the carbon material is increased, resulting in the assembled internal hybrid battery being able to run only 3600 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.09ml / (wh·h).
[0066] Comparative Example 5
[0067] According to the requirements of Example 1, without changing other conditions, the volume ratio of alcohol to water in step 1, 1. the mixed solution of water and ethanol is 1000:1 to form a solution. Due to the lack of induction of γ-butyrolactone by alcohol polar organic compounds, the amount of γ-butyrolactone introduced into the activated carbon is too low. After testing, the organic matter in the prepared carbon material accounts for 0.1% of the entire material, and the assembled internal hybrid battery can only run 10800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.37ml / (wh·h).
[0068] Comparative Example 6
[0069] According to the requirements of Example 1, without changing other conditions, the amount of sulfuric acid solution added in step 1 and 2 in the preparation step of the carbon composite material is changed to 0 ml. The purpose of adding sulfuric acid solution is to adjust the pH value of the mixed solution. In this comparative example, γ-butyrolactone cannot be adsorbed on the surface and pores of the carbon material in a closed-loop form without adding sulfuric acid solution. The closed-loop γ-butyrolactone has a strong binding force with the carbon material. Without adding sulfuric acid solution, a large amount of γ-butyrolactone cannot enter the pores of the carbon material or adsorb on its surface, causing the effect of the composite material to be greatly attenuated. After testing, the organic matter in the prepared carbon material accounts for 0.5% of the entire material. The assembled internal hybrid battery can run 7200 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.40 ml / (wh·h).
[0070] Comparative Example 7
[0071] According to the requirements of Example 1, without changing other conditions, step 1, 1. γ-butyrolactone was replaced with the same mass of isolipin (molecular weight: 1129). Since it cannot be fully dissolved in a mixed solution of water and ethanol, and the molecular weight is too large to fully open or close the ring during the pH environment change, the organic matter in the prepared carbon material accounts for 0.3% of the entire material, and the assembled internal hybrid battery can only run 10800 cycles in the normal temperature life test. The gas production rate of the assembled lead-carbon battery in a room temperature environment is 0.33ml / (wh·h).
[0072] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A carbon material, characterized in that: The carbon material contains organic matter containing carbon rings; The content of the carbon ring-containing organic matter in the carbon material is 1 to 30 wt %.
2. The carbon material according to claim 1, characterized in that The molecular weight of the carbon ring-containing organic matter is 90-500.
3. The carbon material according to claim 1, characterized in that The carbocyclic organic matter is selected from at least one of a carbocyclic lactone organic matter and a carbocyclic amide organic matter; The carbocyclic lactone organic substance is selected from at least one of γ-butyrolactone, γ-valerolactone, coumarin, and thiamin; The carbon ring-containing amide organic compound is selected from at least one of benzamide, dansamide, o-amide and furamide.
4. A method for preparing the carbon material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The raw materials containing organic matter containing carbon rings, activated carbon material, sulfuric acid and solvent are mixed and dried to obtain the carbon material.
5. The preparation method according to claim 4, characterized in that: The following steps are involved: The organic matter containing the carbon ring is mixed with a solvent to obtain a mixed solution, and then sulfuric acid and an activated carbon material are added to the mixed solution in sequence, stirred, and dried to obtain the carbon material.
6. The preparation method according to claim 4, characterized in that: The activated carbon material is selected from at least one of coal-based activated carbon, wood-based activated carbon, synthetic activated carbon, and biomass activated carbon; The specific surface area of the activated carbon material is 300 to 3000 m 2 / g; The solvent is a mixed solution of water and ethanol; In the solvent, the volume ratio of water to ethanol is 1:0.01-100.
7. The preparation method according to claim 4, characterized in that: The ratio of the carbon ring-containing organic matter to the solvent is 0.01-50 g: 20-2000 ml; The usage ratio of the sulfuric acid to the solvent is 0.1-100 ml: 20-2000 ml; The usage ratio of the carbon ring-containing organic matter to the activated carbon material is 0.01-50g:1-1000g.
8. The preparation method according to claim 4, characterized in that: The drying temperature is 40-150°C; The drying time is 1 to 48 hours.
9. An electrode, characterized in that: The electrode contains the carbon material according to any one of claims 1 to 3.
10. A lead-acid battery, characterized in that: The lead-acid battery comprises the electrode according to claim 9.
Citation Information
Patent Citations
Lead-carbon composite material
CN102074702A
Preparation method of lead crystal carbon storage battery
CN106207279A
Negative electrode lead paste of power lead-acid storage battery and preparation method of negative electrode lead paste
CN114005979A
Activated carbon material and electric double-layer capacitor
JP2002237433A
Method of producing active carbon for capacitor and active carbon
JP2012049389A